Gambaran Tingkat Pengetahuan dan Tingkat Kecemasan Mahasiswa Tingkat Tiga Prodi DIII Kebidanan Poltekkes Karya Husada dalam Menghadapi Ujian Kompetensi Exit Exam sesuai Permendikbud No 2 Tahun 2020 - Amri Wulandari (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2023)
Anxiety is an emotional state with the onset of discomfort in third-grade students of midwifery, and is a vague experience accompanied by feelings of helplessness and uncertainty caused by something that is not yet clear, because students will face the exit exam competency test for the first time. The purpose of the study in general is to find out the level of knowledge and anxiety levels of students facing the exit exam competency test. This type of research is descriptive analytics with a cross sectional approach, the population is a third-level student midwifery program, numbering 21 respondents, using primary data. Research time from June to December 2021. The results showed that the majority of students aged 21 years as many as 47.6% or 10 students. The majority of knowledge about the exit exam competency test has knowledge of either 80.95% or 17 students, and who have sufficient knowledge as much as 19.05% or 4 students, the majority of student anxiety levels are not anxious 80.95% or 17 students, mild anxiety levels 4.76% or 1 student, and severe anxiety levels 9.52% or 2 students, and very severe anxiety levels 4.76% or 1 student. Anxiety should be handled properly immediately otherwise it will have an impact on the student that is unable to concentrate properly so that it will not get maximum grades.